Growth-enhancing taxes - David de Padua; Mae Hyacinth Kiocho; Donghyun Park (Asian Development Bank (ADB), 2024)
We investigate the conditions under which tax revenues can enhance economic growth. Using a newly constructed dataset consisting of 135 economies and spanning the period 1990-2019, we study how changes in tax revenues impact economic growth using a panel vector autoregression (PVAR) model. Tax revenues have a persistent positive impact on growth, and the association is especially pronounced in emerging economies. Strict inflation targeting, low-inflation, flexible exchange rates, a more developed financial sector, higher investment rates, and strong governance reinforce the growth-enhancing effect of taxes, but these results are conditional on the income level of the economy. Our findings imply that the effect of taxes on growth should be evaluated within macroeconomic and structural constraints.
Keywords: H20; 330; taxes; growth